PENGATURAN HAK NARAPIDANA DALAM MENDAPATKAN KEBUTUHAN BIOLOGIS SELAMA MASA HUKUMAN DIPENJARA MENURUT HUKUM PIDANA INDONESIA - As shidqie, Maulana Ghalib; Artina, Dessy; Erdiansyah, Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
One of the negative consequences is the deprivation of a person's normal sexual life, so that it is notuncommon for problems such as homosexuality and masturbation among the convicted to occur frequently.Sexual intercourse is a need, just like any other need that demands fulfillment. A prisoner who is in acorrectional facility should get sexual needs. Especially inmates who are married. As is well known, thefulfillment of biological desires is indeed a basic need for humans, both men and women. But while inprison, of course the fulfillment of this desire was disturbed. Physiological needs, such as food, drink, restor sleep, and sex, are the first and foremost needs that must be met by each individual. With these needsfulfilled, people can maintain life from death. In the context of prisoners, the government regulates how thefulfillment of basic physical needs, especially nutritional needs, is met properly, but other physical needssuch as sexual needs have not been explicitly regulated.This type of research is a normative legal research that is research conducted with a literature study orliterature study in finding data. This research is descriptive in nature which provides detailed and detaileddata on existing problems. In this paper using qualitative data analysis which means to explain andconclude about the data that has been collected by the author. This research uses secondary data orscientific data that has been codified.The results of this study explain that in Law Number 12 of 1995 concerning Corrections, especially inArticle 14 paragraph (1), it regulates the rights of prisoners during their sentence in prison, but in thatarticle does not regulate biological needs, especially sexual needs of prisoners during sentence in prison.Sexual needs, both empirically and theoretically, are important needs for biologically mature humans,which, if not fulfilled, will result in many sexual deviations between prisoners during their sentence inprison. Furthermore, the practice of romance booths has been carried out in Indonesian prisons, this isevident in the case of the convict fahmi Darmawansyah who runs the business of love room facilities byrenting out to other inmates for sexual activity by paying a sum of money. From this case, it is clear thatthe practice of romance booths is carried out illegally because the legal regulations that discuss theprovision of romance booths do not yet exist in Indonesia. The idea that the author offers is to regulate thebiological rights of prisoners during their sentence in prison by implementing or applying legal and freeconjugal visit facilities for inmates who are married with the rules and mechanisms stipulated by thelegislators later.Keywords: Convict – Biological Needs - Criminal Law